2003
DOI: 10.1057/palgrave.hep.8300021
|View full text |Cite
|
Sign up to set email alerts
|

Higher Education in Nigeria: A Status Report

Abstract: The government of Nigeria recently initiated higher education policy reforms intended to bring its university system more in line with international good practices. The reforms promote increased institutional autonomy, greater system differentiation, strengthened governance, and mechanisms for quality assurance. They seek to create a more flexible and responsive system of university teaching and research that, over time, will contribute increasingly to national innovation capacities, productivity gains, and ec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
71
0
2

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 116 publications
(74 citation statements)
references
References 13 publications
1
71
0
2
Order By: Relevance
“…Adamolekun (2007) therefore opined that policy reform in this direction would need to be accompanied with appropriate mix of scholarships and loans that would ensure that no Nigerian who is qualified for University education is denied the opportunity because of his/her inability to pay prescribed fees. In view of this, Okebukola (2006) suggested that more creative financing strategies are needed in order for Nigerian Universities to offset the likely risks of declining educational quality, resource efficiency and learning effectiveness that currently confront it (Saint, Hartnett and Strassner, 2003). The danger in this is that the teaching and research mission of Universities would drop in priority and would become distorted because of the search for entrepreneurial revenue.…”
Section: Fundingmentioning
confidence: 99%
See 1 more Smart Citation
“…Adamolekun (2007) therefore opined that policy reform in this direction would need to be accompanied with appropriate mix of scholarships and loans that would ensure that no Nigerian who is qualified for University education is denied the opportunity because of his/her inability to pay prescribed fees. In view of this, Okebukola (2006) suggested that more creative financing strategies are needed in order for Nigerian Universities to offset the likely risks of declining educational quality, resource efficiency and learning effectiveness that currently confront it (Saint, Hartnett and Strassner, 2003). The danger in this is that the teaching and research mission of Universities would drop in priority and would become distorted because of the search for entrepreneurial revenue.…”
Section: Fundingmentioning
confidence: 99%
“…Aina (2007) noted that government provides about 90 percent of the funds required for the administration of Universities and welcomes individuals, other organizations as well as individual Universities in providing the remaining 10 percent. Saint, Hartnett and Strassner (2003), observed that in practice, government is unable to adequately fund the University system and the current funding strategy does not serve the country's long term development interests. Consequently, funding short falls have been the norm for many years as enrollments have increased more quickly than the government's capacity to maintain its proportional financial support.…”
Section: Fundingmentioning
confidence: 99%
“…In recent times, the level of job performance, international comparability and competitiveness of Nigerian university graduates have become burning issues. In fact, observers believe that the quality of Nigerian tertiary institutions are plummeting, a condition Saint, Hartnett, and Strassner (2003) described as"...a precipitous fall in the quality of university education…" (p. 364).…”
Section: Quality In Nigerian Universitiesmentioning
confidence: 99%
“…At the primary and secondary levels, cases of alcohol consumption, rape, wearing of unauthorized and assorted dresses, smoking of Indian hemp and cigarettes, staying in hostel during lesson, stealing, truancy, are few among the negative attitudes of pupils/students (Nwana, 1998). At the tertiary level, student unrest and cultism are also prevalent (Saint, Hartnett and Strassner, 2003;Akpabio, 2001). Among the factors behind the cases of indiscipline are school based factors such as: inadequate teachers; professional incompetence of teachers; undue familiarity of teachers and students; moral laxity of teachers which prevents them from becoming role models to pupils/students; lack of motivation or encouragement to teachers; frequent transfer of teachers and discrimination by school principal just to mention few (Afolabi, 1998;Yaroson, 2004).…”
Section: Indiscipline Of Pupils and Studentsmentioning
confidence: 99%
“…Notable among these crises are: policies instability, poor implementation of policies, inadequate funding, limited access to school, inadequate infrastructural facilities, improper planning and implementation, corruption, rising population, unemployment, wastage (repetition and dropout) just to mention few (Adeyemi & Ige,2002;Ajayi & Shofoyeke, 2003;Okebukola, 2002;Saint, Hartnett & Strassner, 2003;Obanya, 2004;Ige, 2011;Ibeh, 2009). Of all the crises however, those that centre round teachers are significant and worthy of attention because of their invaluable roles in the education process.…”
Section: Introductionmentioning
confidence: 99%